GROWTH OF RAMIN (Gonystylus bancanus (Miq) Kurz.) PLANTATION ON VARIOUS PEAT SWAMP FORESTS IN INDONESIA - Rostiwati, Tati; Murniati, Murniati; Hendromono, Hendromono (Indonesian Journal of Forestry Research, 2007)
Ramin (Gonystylus bancanus (Miq) Kurz.) is a trade name of timber produced from a group of Gonystylus species. It is a well-known species because of its high timber quality and value. Ramin natural population has been decreasing sharply since the last two decades due to over exploitation, and nowadays leads to extinction. The objective of  this research was to analyze the growth of ramin plantation on various sites.  Data were collected from February to April 2005 through field survey on five sites of peat-swamp forest areas in four provinces, Riau, Jambi, West and Central Kalimantan. The result showed that ramin annual early growth varied across sites.   It grew better on deep peat soil (3 - 4 m in depth) and under moderate shading (55 - 60%) during early growth. The highest early height growth (52.27 cm/year) occurred at Sei Bakau, West Kalimantan.  Whereas, it highest early diameter growth (0.73 cm/year) was found at Rokan Hilir, Riau. The characteristics of site are very important for a successful growth of ramin plantation, including peat depth and level of shading. Annual early growth of ramin as along in line with increasing of the plant age, namely a four- times increase of plant age (from 1.6 - 2 years to 6.5 - 7.3 years), the annual early height and diameter growth decreased until they reached a half and one third of the starting values. Since the growth of ramin is very slow, it is necessary to find and develop technologies to accelerate growth rate of  the ramin plants. Application of mycorrhizal fungal inoculum is a promising technology, but their role in promoting ramin growth and the needed cost must be tested and analyzed under various conditions of the peat-swamp soils in Indonesia.